(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: The aim of this study was to determine the efficacy of expressed breast milk (EBM) alone or in combination with oral paracetamol for pain reduction during retinopathy of prematurity (ROP) screening. Methods: A randomized control trial was conducted in two departments of Bangabandhu Sheikh Mujib Medical University. A total of 60 preterm neonates who underwent ROP screening were randomized into three equal groups. Group A got nesting and swaddling as per institutional protocol (control). Group B received 2 ml EBM two minutes prior to the ROP screening and Group C received 15 mg/kg syrup paracetamol 30 minutes prior to the ROP screening and EBM like Group B. Premature infant pain profile (PIPP) scores was used prior, during and 2 minutes after ROP screening procedure. Results: The three groups were similar in terms of baseline characteristics. The mean (standard deviation) PIPP scores during the procedure were 16.4 (1.1), 15.0 (1.8) and 13.4 (1.8) in control, EBM, and EBM with paracetamol groups respectively. The PIPP scores were significantly lower in the EBM and EBM with paracetamol groups during the procedure compared to control group. In the EBM and EBM with paracetamol groups, the mean difference in PIPP scores (between before and during the procedure) was also substantially lower. Conclusion: Breast milk alone or in combination with paracetamol can reduce significant pain during ROP screening than control group.